Artificial graphite material for negative electrodes of lithium-ion secondary batteries and its manufacturing method
Patent Information
- Application Number
- JP2022531936
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2021-06-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-06-18
AI Technical Summary
【0012】 本発明は、-10℃の低温で充放電を繰り返しても放電容量が劣化し難い、リチウムイオン二次電池負極用人造黒鉛材料、及びその製造方法、並びにリチウムイオン二次電池用負極、及びリチウムイオン二次電池を提供するものである。
Smart Images

Figure 0007644116000004 
Figure 0007644116000001 
Figure 0007644116000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an artificial graphite material for a negative electrode of a lithium ion secondary battery, and a method for producing the same. This application claims priority based on Japanese Patent Application No. 2020-105303, filed on June 18, 2020, the contents of which are incorporated herein by reference. [Background technology]
[0002] Lithium-ion secondary batteries are used in automobiles and for industrial purposes such as power storage in grid infrastructure. Graphite such as artificial graphite material is used as the negative electrode material of lithium ion secondary batteries (see, for example, Patent Document 1).
[0003] Batteries for automotive applications are used over a wide temperature range, from low temperatures below 0°C to high temperatures above 60°C. However, lithium-ion secondary batteries, which use graphite as the negative electrode material, have an issue in that lithium metal is easily precipitated on the negative electrode when charged at low temperatures below 0°C. When lithium metal precipitates on the negative electrode, the number of lithium ions that can move between the positive and negative electrodes decreases, causing the capacity of the lithium-ion secondary battery to deteriorate.
[0004] It has been reported that in a state in which lithium metal is not deposited on the negative electrode, capacity degradation progresses due to the difference in charge / discharge efficiency between the positive electrode and the negative electrode (see, for example, Non-Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5415684 [Non-patent literature]
[0006] [Non-Patent Document 1] 51st Battery Symposium Abstracts 3G15 (November 8, 2010) [Non-Patent Document 2] "Fuel Association Journal" Vol. 58, No. 642 (1979), pp. 257-263 [Non-Patent Document 3] Carbon, 1981(No.105), p73-81 Summary of the Invention [Problem to be solved by the invention]
[0007] The challenge for lithium-ion batteries that use graphite as the negative electrode material is how to suppress capacity degradation due to charging and discharging at low temperatures below 0° C. In particular, industrial lithium-ion batteries used in automobiles and for power storage in grid infrastructure are required to operate over a wide temperature range, so there is a demand for lithium-ion secondary batteries and their negative electrode graphite materials that can suppress capacity degradation even when charged and discharged at even lower temperatures.
[0008] The present invention has been made in consideration of the above circumstances, and provides an artificial graphite material for a negative electrode of a lithium ion secondary battery, which is resistant to deterioration in discharge capacity even when repeatedly charged and discharged at a low temperature of -10°C, a method for producing the same, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Means for solving the problem]
[0009] The present invention includes the following aspects. [1] A method for producing an artificial graphite material for a negative electrode of a lithium ion secondary battery, comprising the steps of: coking the feed oil composition by a delayed coking process to produce a feed coal composition; heat-treating the raw coke composition to obtain a heat-treated raw coke composition; pulverizing the heat-treated raw coal composition to obtain raw coal powder; graphitizing the raw coal powder to obtain graphite powder; and grinding the graphite powder. The raw coal powder has a volatile content of less than 3.71% and a true density of 1.22 g / cm 3 Super 1.73g / cm 3The present invention relates to a method for producing an artificial graphite material for a negative electrode of a lithium ion secondary battery, the method comprising the steps of:
[0010] [2] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to [1] above, wherein the heat treatment temperature in the step of obtaining the heat-treated raw coke composition is 500° C. or more and 700° C. or less. [3] The method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to [1] or [2] above, wherein the raw oil composition has a normal paraffin content of 5 to 20 mass% and an aromatic index fa determined by the Knight method of 0.3 to 0.65. [4] A negative electrode for a lithium ion secondary battery, comprising the artificial graphite material obtained by the method for producing the artificial graphite material according to any one of [1] to [3] above. [5] A lithium ion secondary battery having the negative electrode according to [4] above.
[0011] [6] Nitrogen adsorption specific surface area S(BET) is 2.5-6.2m 2 / g, The X-band electron spin resonance method showed that the absorption spectrum originating from carbon radicals appeared at around g = 2.0. The ratio of the spin density I(4.8K)(spins / g) and S(BET), calculated from the signal intensity at 4.8 K, was 5.2 × 10 17 ~6.8×10 17 spins / m 2 1. An artificial graphite material for a negative electrode of a lithium ion secondary battery, comprising: Effect of the Invention
[0012] The present invention provides an artificial graphite material for a negative electrode of a lithium ion secondary battery, the discharge capacity of which is not easily deteriorated even when the battery is repeatedly charged and discharged at a low temperature of -10°C, a method for producing the same, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view showing an example of a lithium-ion secondary battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The artificial graphite material for a lithium ion secondary battery negative electrode, the manufacturing method thereof, the lithium ion secondary battery negative electrode, and the lithium ion secondary battery according to the present invention will be described in detail below. Note that the present invention is not limited to the following embodiments.
[0015] <<Artificial graphite material for negative electrodes of lithium-ion secondary batteries>> The artificial graphite material of this embodiment satisfies all of the following conditions (1) to (2). Moreover, the artificial graphite material of this embodiment preferably satisfies all of the following conditions (1) to (3). (1) Nitrogen adsorption specific surface area S(BET) is 2.5 to 6.2 m 2 / g. (2) The X-band electron spin resonance spectrum shows an absorption spectrum originating from carbon radicals appearing around g = 2.0. The ratio of the spin density I(4.8K)(spins / g) and S(BET), calculated from the signal intensity at 4.8 K, is 5.2 × 10 17 ~6.8×10 17 spins / m 2 It is. (3) The crystallite size L(112) calculated from the (112) diffraction line measured by wide-angle X-ray diffraction is 4 to 30 nm.
[0016] The nitrogen adsorption specific surface area S(BET) under the above condition (1) is the nitrogen adsorption specific surface area (m2) measured and calculated in accordance with JIS Z 8830 (2013) "Method for measuring the specific surface area of powders (solids) by gas adsorption". 2 / g). The specific surface area measured and calculated by this method will hereinafter be abbreviated as "specific surface area".
[0017] The I(4.8K) in the above condition (2) is the spin density (spins / g) calculated from the signal intensity of the absorption spectrum originating from carbon radicals appearing near g=2.0 when ESR measurements are performed by placing a graphite material in a sample tube, evacuating the tube, and then sealing He gas in the sample tube under the following conditions: X-band microwave (9.60GHz), intensity 1mW, central magnetic field 3412G, magnetic field modulation 100kHz, and measurement temperature 4.8K. The ESR spectrum is usually obtained as a first derivative spectrum, and when integrated once, it becomes an absorption spectrum, and when integrated twice, the signal intensity is obtained. The magnitude of the spin density calculated from the signal intensity at this time is an index representing the unpaired electron density in the substance. Therefore, the ratio I(4.8K) / S(BET) in the above condition (2) is an index representing the unpaired electron density per unit surface area, and will be abbreviated as I(4.8K) / S(BET) below.
[0018] In the above condition (3), the crystallite size L(112) calculated from the (112) diffraction line measured by wide-angle X-ray diffraction is L(112) measured and calculated in accordance with JIS R 7651 (2007) "Method of measuring lattice constant and crystallite size of artificial graphite material". Hereinafter, L(112) measured and calculated by this method may be abbreviated as L(112).
[0019] The inventors have conducted extensive research focusing on the crystallite size, nitrogen adsorption specific surface area, and I(4.8K) / S(BET) of the artificial graphite material, and have found that by producing a lithium ion secondary battery having a negative electrode containing an artificial graphite material that satisfies all of the above conditions (1) to (2), preferably all of the above conditions (1) to (3), it is possible to suppress deterioration of the discharge capacity when charging and discharging are repeated at a temperature of -10°C or lower, and have completed the present invention.
[0020] The above condition (1) "Nitrogen adsorption specific surface area is 2.5 to 6.2 m 2 Lithium-ion secondary batteries with negative electrodes containing artificial graphite material with a nitrogen adsorption specific surface area of 2.5 m are less likely to deteriorate in discharge capacity even when the charge-discharge cycle is repeated at low temperatures of -10°C or less. 2When the nitrogen adsorption specific surface area is 6.2 m / g or more, the effect of suppressing the deposition of lithium metal on the negative electrode due to the large nitrogen adsorption specific surface area can be sufficiently obtained. 2 In the case of artificial graphite materials with a specific surface area of 0.1 to 1.0 kPa (1.0 to 1.0 g / g) or less, the intercalation reaction of lithium ions into graphite crystals when charged at low temperatures of -10°C or less is not inhibited by steric hindrance caused by unorganized carbon on the particle surfaces resulting from the pulverization of graphite powder during production.
[0021] Here, unorganized carbon refers to an aggregate structure made up of carbon atoms that are not incorporated into the carbon hexagonal network plane. Although its chemical structure is not entirely clear, it is thought to be a complex aggregate structure made up of dangling bonds that are generated when the chemical bonds that make up the hexagonal network plane are broken by the mechanical energy of crushing (see, for example, "Carbon Terminology Dictionary," pp. 354-355 (published by Agne Shofusha, October 5, 2000)). For this reason, unorganized carbon acts as a steric hindrance to the reversible intercalation reaction into graphite that accompanies charging and discharging, making it easier for lithium metal to precipitate during charging. As mentioned above, unorganized carbon is generated by the crushing of graphite powder during manufacturing, and is therefore 6.2m 2 When the carbon is ground to less than 1 / g, the contribution of unorganized carbon as a steric hindrance is small.
[0022] In contrast, the graphite powder used during manufacturing has a nitrogen adsorption specific surface area of 6.2 m 2 Artificial graphite pulverized to a size exceeding 100000000 / g has a large amount of unorganized carbon introduced into the particle surface, which contributes to steric hindrance to the reversible intercalation reaction of lithium ions. In particular, charging at low temperatures below -10°C, where the viscosity of the electrolyte decreases, is not preferable because lithium ions tend to precipitate.
[0023] The above condition (2) "has an absorption spectrum originating from carbon radicals appearing at around g = 2.0 by electron spin resonance using X-band, and the ratio I(4.8K) / S(BET) of the spin density I(4.8K) calculated from the absorption intensity at a temperature of 4.8K to the above S(BET) is 5.2 × 10 17 ~6.8×10 17Lithium ion secondary batteries having a negative electrode containing an artificial graphite material are less likely to deteriorate in discharge capacity even when charge / discharge cycles are repeated at low temperatures of -10°C or lower. Here, the above I(4.8K) is an index representing the spin density (spins / g) of unpaired electrons (localized electrons) contained in unorganized carbon introduced by pulverizing graphite powder during production. I(4.8K) / S(BET) is the amount of unorganized carbon introduced per unit area (spins / m), which is mainly introduced on the particle surface. 2 The reasons for this are explained in detail below.
[0024] ESR measurement is a spectroscopic analysis that observes the transition between levels that occurs when unpaired electrons are placed in a magnetic field. When a magnetic field is applied to a material with unpaired electrons, the energy levels of the material are divided into two by the Zeeman effect. Measurements are performed by sweeping the magnetic field under microwave irradiation, and as the applied magnetic field increases, ΔE, the energy division interval, increases. When ΔE becomes equal to the energy of the irradiated microwave, resonance absorption is observed, and the ESR spectrum is obtained by detecting the amount of energy absorbed at this time. ESR spectra are usually obtained as first-order differential spectra, and when integrated once, they become absorption spectra, and when integrated twice, the signal intensity is obtained. The magnitude of the signal intensity at this time is an index that represents the density of unpaired electrons in the material. In the crystals of graphite materials, there are two types of unpaired electrons: localized electrons and conduction electrons. In other words, in ESR measurements of graphite materials, the sum of the resonance absorption of microwaves by these two types of unpaired electrons is observed as the ESR spectrum. The signal intensity obtained by integrating the ESR spectrum twice is an index that indicates the magnitude of the unpaired electron density, which is the sum of the conduction electron density and the localized electron density. Here, the conduction electrons in graphite materials are unpaired π electrons that spontaneously appear in relation to the number of rings that form the hexagonal network plane and their bonding form, and can move freely within the hexagonal network plane (see, for example, Carbon 1966 No.47 30-34, 1967 No.50 20-25).
[0025] On the other hand, localized electrons are localized electrons that exist on the edge surface of the hexagonal net planar laminate, and are immobile electrons. In addition, while the signal strength of the resonance absorption by the conduction electrons does not depend on temperature, the signal strength of the resonance absorption by the localized electrons increases in inverse proportion to the measurement temperature T. For example, in the ESR measurement of a carbon material in the temperature range of 4.2K≦T≦300K, when the measurement temperature is gradually lowered from 300K, it has been reported that the absorption of microwaves by localized electrons begins to be observed around 50K, and in the low temperature region below 50K, the signal strength by the localized electrons increases sharply in inverse proportion to the measurement temperature T (see, for example, Carbon 1996 No.175 249-256). From these facts, it can be said that the spin density I(4.8K) calculated from the absorption intensity at a temperature of 4.8K is an index that represents the density of localized electrons. Furthermore, since the localized electrons introduced by pulverization of graphite powder during production are introduced onto the fracture surfaces, i.e., the particle surfaces, the ratio I(4.8K) / S(BET) of I(4.8K) to the nitrogen adsorption specific surface area S(BET) can be regarded as an index representing the amount of localized electron spins per unit area on the particle surface.
[0026] The artificial graphite material of this embodiment satisfies the above condition (2). That is, the artificial graphite material has an absorption spectrum originating from carbon radicals appearing near g=2.0 by electron spin resonance using X-band, and the ratio I(4.8K) / S(BET) of the spin density signal intensity I(4.8K) calculated from the absorption intensity at a temperature of 4.8K to the S(BET) is 5.2×10 17 ~6.8×10 17 In particular, highly crystalline graphite powder having a crystallite size L(112) of 4 to 30 nm, which satisfies the above condition (3), has a nitrogen adsorption specific surface area of 2.5 to 6.2 m, which is the volumetric surface area of the above condition (1). 2 / g, the regularity of the three-dimensional arrangement of carbon atoms on the fracture surface is greatly reduced, and the localized electron density per unit area, i.e., I(4.8K) / S(BET), increases, usually reaching 7.0×10 17 (spins / m 2 ) or more.
[0027] In contrast, the artificial graphite of this embodiment has an I(4.8K) / S(BET) of 5.2×10 17 ~6.8×10 17 That is, the artificial graphite of this embodiment satisfies the localized electron density (spins / m 2 ), that is, the amount of unorganized carbon introduced to the particle surface is low. Because there is little unorganized carbon that acts as a steric hindrance to the reversible intercalation of lithium ions, lithium metal is unlikely to precipitate even when charging at low temperatures of -10°C or lower, and deterioration of discharge capacity when charging and discharging are repeated in that temperature range can be suppressed.
[0028] I(4.8K) / S(BET) is 5.2×10 17 It is possible to manufacture artificial graphite material with a carbon content of less than 10 ... 17 ~6.8×10 17 Limited to.
[0029] The artificial graphite material having the above condition (3) "L(112) is 4 to 30 nm" has a highly developed crystal. The artificial graphite material having L(112) of 4 to 30 nm has a degree of graphitization suitable for the negative electrode of a lithium ion secondary battery. Since the larger the L(112), the larger the reversible capacity, it is preferable that the L(112) of the artificial graphite material is 4 nm or more. The artificial graphite material having L(112) of less than 4 nm may have insufficient development of the crystal structure. For this reason, a lithium ion secondary battery having a negative electrode containing an artificial graphite material having L(112) of less than 4 nm may have a small capacity and may be undesirable (for example, see "Negative Electrode Carbon Material for Lithium Ion Secondary Batteries" p. 3-4 (Realize Co., Ltd., published October 20, 1996)).
[0030] <<Method of manufacturing artificial graphite material for negative electrodes of lithium-ion secondary batteries>> The artificial graphite material of this embodiment can be produced, for example, by the production method described below. That is, the method for producing the artificial graphite material for a lithium ion secondary battery negative electrode according to the present embodiment is as follows: A step of coking the raw oil composition by a delayed coking process to produce a raw coal composition (hereinafter also referred to as "step A"); A step of heat-treating the raw coke composition to obtain a heat-treated raw coke composition (hereinafter also referred to as "step B"); A step of pulverizing the heat-treated raw coal composition to obtain raw coal powder (hereinafter also referred to as "step C"); A step of graphitizing the raw coal powder to obtain graphite powder (hereinafter also referred to as "step D"); The method includes at least a step of pulverizing the graphite powder (hereinafter also referred to as "step E"). In the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of this embodiment, the volatile content of the raw coal powder is less than 3.71%, preferably 0.1% or more and 3.6% or less, and the true density of the raw coal powder is 1.22 g / cm 3 Super 1.73g / cm 3 and preferably less than 1.26 g / cm 3 More than 1.68g / cm 3 The following is the result.
[0031] The volatile content of the raw coal powder is the volatile content [mass fraction (%)] calculated in accordance with "7. Volatile content determination method" in "7.2 Vertical tubular electric furnace method" and "b) In the case of coke" described in "Coals and cokes - Methods of proximate analysis" of JIS M 8812 (2004). The volatile content calculated by this method is hereinafter abbreviated as "volatile content".
[0032] The true density of the raw coal powder is calculated in accordance with "7.3 True density test method" in "7. Density and porosity test method" described in "Cokes - Test methods" of JIS K 2151 (2004). 3 The true density calculated by this method is hereinafter abbreviated as "true density".
[0033] When this artificial graphite material is used in the negative electrode of a lithium-ion secondary battery, deterioration of the discharge capacity is suppressed even when charging and discharging are repeated at a low temperature of -10°C. This is presumably because the fracture initiation points generated by the combination of the heat treatment of the raw coal composition and the subsequent pulverization remain even after graphitization, and pulverization occurs starting from these fracture initiation points, resulting in a small amount of unorganized carbon being introduced into the fracture surface.
[0034] The heat treatment of the raw coke composition reduces the volatile content, but creates volatile evaporation paths, i.e., pores of various sizes, large and small, in a curved shape, on the surface and in the internal bulk. Due to the mechanical energy of the crushing after the heat treatment, small pores grow as cavities (cracks), and large pores grow as cavities and then break (crush). The cavities thus grown remain as lattice defects even after graphitization, and act as fracture initiation points in the subsequent crushing. Lattice defects (the cavities) remain on the fracture surface generated by such crushing, and chemical bonds are broken in the fracture areas other than the lattice defects. Since chemical bonds are not broken on the entire fracture surface, the amount of unorganized carbon introduced by crushing is smaller on the fracture surface generated from the lattice defects as the fracture initiation points than on the fracture surface generated in the absence of lattice defects. Since there is little unorganized carbon that acts as a steric hindrance to the reversible intercalation of lithium ions, lithium metal is less likely to precipitate even when charging at low temperatures of -10°C or below, and deterioration of discharge capacity when charging and discharging is repeated in that temperature range can be suppressed.
[0035] The true density of the raw coal composition produced by subjecting the raw oil composition to a delayed coking process is usually 1.1 to 1.4 g / cm 3 The volatile content is usually 5 to 15% (Non-Patent Document 2). Typical changes caused by heat treating a raw coke composition with such properties are a decrease in the volatile content and an increase in the true density. The reason for the decrease in the volatile content is that the volatile content contained in the raw coke composition is a reaction product of the raw oil composition remaining in a state where the thermal decomposition and polycondensation reaction are insufficient in the delayed coking process, and therefore disperses during the subsequent heat treatment. The reason for the increase in true density is that the thermal decomposition and polycondensation reaction proceed further due to the heat treatment. A raw coke composition with such properties is heat treated and then pulverized to obtain a raw coke powder with a volatile content of less than 3.71%, preferably 0.1% to 3.6%, and the true density of the raw coke powder is 1.22 g / cm. 3 Super 1.73g / cm 3 less than 1.26 g / cm 3 More than 1.68g / cm 3or less, a large amount of the fracture initiation points of an appropriate size will be introduced, so that the artificial graphite material for a lithium ion secondary battery negative electrode obtained thereafter can suitably suppress deterioration in discharge capacity even when repeatedly charged and discharged at -10°C.
[0036] When the heat treatment reaction of the raw coal composition proceeds too far, for example, the volatile content of the raw coal powder is less than 0.1% and the true density is 1.68 g / cm 3 If the size is larger, the growth of the hexagonal net planes of carbon atoms becomes too large, so that even if the material is subsequently pulverized, it is not possible to introduce the fracture initiation points of a suitable size. Therefore, the discharge capacity of the artificial graphite material obtained thereafter is significantly degraded when the material is repeatedly charged and discharged at -10°C.
[0037] Conversely, if the heat treatment of the raw coal composition is insufficient, the volatile content of the raw coal powder is 3.7% or more and the true density is 1.22 g / cm 3 If the temperature is less than 100°C, only compounds with relatively low molecular weights that are not sufficiently pyrolyzed or polycondensed during the delayed coking process will evaporate, and no fracture initiation points of a suitable size will be formed. Therefore, the discharge capacity of the artificial graphite material obtained thereafter will be significantly degraded when it is repeatedly charged and discharged at -10°C. Therefore, the volatile content of the heat-treated raw coal powder is less than 3.71% and the true density is 1.22 g / cm. 3 Super 1.73g / cm 3 Limited to less than.
[0038] Hereinafter, each step of the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to this embodiment will be described in detail.
[0039] [Process A] Examples of the feedstock oil composition in step A include heavy oils such as bottom oil of fluid catalytic cracking oil (FCC DO), heavy oil that has been subjected to advanced hydrodesulfurization treatment, vacuum distillation residual oil (VR), coal liquefaction oil, coal solvent extraction oil, atmospheric distillation residual oil, shale oil, tar sand bitumen, naphtha tar pitch, coal tar pitch, ethylene bottom oil, etc. Also, as the feedstock oil composition, any of the above heavy oils that have been subjected to various treatments such as hydrorefining may be used.
[0040] As the feedstock oil composition in step A, it is particularly preferable to use heavy oil that contains an appropriate amount of saturates and normal paraffins and has been subjected to advanced hydrodesulfurization treatment. As the feedstock oil composition, a single heavy oil may be used, or two or more types of heavy oils may be mixed and used. When two or more types of heavy oils are mixed and used as the feedstock oil composition, the blending ratio of each heavy oil can be appropriately adjusted according to the properties of each heavy oil. The properties of each heavy oil vary depending on the type of crude oil, the processing conditions until the heavy oil is obtained from the crude oil, and the like.
[0041] It is preferable to use a raw oil composition in step A that contains a component that generates a good bulk mesophase during coking treatment and a component that generates a gas that reduces the size of the bulk mesophase when the bulk mesophase is polycondensed to carbonize and solidify.
[0042] In the step A, a component that generates a good bulk mesophase in the feedstock oil composition may be a heavy oil component having an aromaticity index fa within a predetermined range as determined by the Knight method. In the method for producing an artificial graphite material of the present embodiment, the feedstock oil composition used has an aromaticity index fa of preferably 0.30 to 0.65, more preferably 0.35 to 0.60, and even more preferably 0.40 to 0.55 as determined by the Knight method.
[0043] Here, the aromatic index fa is the aromatic carbon fraction calculated by the Knight method. In the Knight method, the carbon distribution is 13 The spectrum of aromatic carbon by C-NMR is divided into three components (A1, A2, A3). Here, A1 is the number of carbon atoms in the aromatic ring (the number of substituted aromatic carbons and half of the unsubstituted aromatic carbons ( 13 C-NMR peak of about 40-60 ppm), and A2 is the remaining half of the unsubstituted aromatic carbon ( 13 C-NMR peak of about 60 to 80 ppm), and A3 is the number of aliphatic carbon atoms ( 13(This corresponds to a peak of about 130 to 190 ppm in C-NMR.) The aromatic index fa is calculated by using A1, A2, and A3 as fa = (A1 + A2) / (A1 + A2 + A3). 13 The C-NMR method is the best method for quantitatively determining fa, which is the most basic quantity of the chemical structure parameters of pitches (see, for example, Non-Patent Document 3).
[0044] When the aromatic index fa of the raw oil composition in step A is 0.3 or more, a combination of the heat treatment of the raw coal composition and the subsequent pulverization treatment forms a fracture initiation point of an appropriate size, and the probability of fracture-like pulverization occurring by pulverization after graphitization is improved. In addition, when the aromatic index fa is 0.65 or less, it is preferable because the bulk mesophase can be limited to a small size by the gas generated during the coking treatment. The boundary between adjacent bulk mesophases is likely to form the fracture initiation point by the subsequent pulverization treatment, so the probability of fracture-like pulverization by the pulverization treatment after graphitization is improved. In contrast, when the aromatic index fa exceeds 0.65, a large number of mesophases are rapidly generated in the matrix during the coking treatment, and the coalescence rate between the mesophases becomes faster than the single growth rate of the mesophase. As a result, the effect of reducing the size of the bulk mesophase by the gas generated during the coking treatment is not sufficiently obtained, and there is a risk that it cannot be limited to a small size. Furthermore, if the aromatic index fa is less than 0.3, the fracture initiation points generated by the pulverization after the heat treatment of the raw coke composition tend to grow large, and the probability of cutting (pulverization) increases sharply. As a result, the number of fracture initiation points remaining after graphitization decreases more than necessary, and it becomes difficult to generate fracture-like pulverization in the pulverization treatment after graphitization, which is not preferable.
[0045] Normal paraffin can be mentioned as a component that generates a gas that reduces the size of the bulk mesophase in the feed oil composition in step A. In the method for producing an artificial graphite material of this embodiment, the feed oil composition used preferably has a normal paraffin content of 5 to 20 mass%, more preferably 10 to 15 mass%.
[0046] The normal paraffin content of the feedstock oil composition in step A means a value measured by a gas chromatograph equipped with a capillary column. Specifically, after calibration using a standard substance of normal paraffin, a sample of non-aromatic components separated by elution chromatography is passed through a capillary column and measured. From this measurement value, the normal paraffin content based on the total mass of the feedstock oil composition can be calculated.
[0047] Normal paraffin contained in the raw oil composition in step A generates gas during coking. This gas plays an important role in restricting the size of the bulk mesophase generated during coking to a small size, restricting the mesophase to a small size. The gas generated during coking also has the function of uniaxially orienting adjacent mesophases restricted to a small size to form a fine structure with selective orientation.
[0048] When the normal paraffin content of the raw oil composition in step A is 5% by mass or more, the bulk mesophase is prevented from growing more than necessary, and carbon hexagonal net planar laminates of moderate size are more likely to be formed. In addition, when the normal paraffin content of the raw oil composition is 20% by mass or less, the amount of gas generated from normal paraffin does not become too large. If excessive gas is generated during the coking treatment, the fracture initiation points generated by the crushing after the heat treatment of the raw coal composition tend to grow large, and the probability of cutting (crushing) increases sharply. As a result, the number of fracture initiation points remaining after graphitization decreases more than necessary, making it difficult to cause fracture-like crushing, which is not preferable.
[0049] As described above, the feed oil composition in step A preferably has a normal paraffin content of 5 to 20 mass% and an aromatic index fa calculated by the Knight method of 0.3 to 0.65. By subjecting such a feed oil composition to a delayed coking process for coking, the boundaries between adjacent mesophases are appropriately introduced, and a combination of the heat treatment of the raw coal composition and the subsequent pulverization treatment forms fracture initiation points of an appropriate size that can remain in the subsequent graphitization treatment. As a result, the probability of fracture-like pulverization occurring by pulverization after graphitization is improved.
[0050] The feed oil composition in step A has a normal paraffin content and an aromatic index fa in the above-mentioned ranges, and a density D of 0.91 to 1.02 g / cm 3 More preferably, the viscosity V is 10 to 220 mm 2 / s is particularly preferred.
[0051] In step A, the method of coking the raw oil composition by the delayed coking process can be, for example, a known method described in Patent Document 1. The method of coking the raw oil composition by the delayed coking process is very suitable for mass production of raw materials for high-quality artificial graphite materials.
[0052] In step A, a delayed coking process is used as a method for coking the raw oil composition. The coking process causes thermal decomposition and polycondensation reactions of the raw oil composition, and a raw coal composition is obtained through a process in which large liquid crystals called mesophase are generated as an intermediate product.
[0053] As for the conditions of the delayed coker, for example, the pressure is preferably 0.1 to 0.8 MPa, and more preferably 0.2 to 0.6 MPa. The temperature is preferably from 400 to 600°C, and more preferably from 490 to 540°C.
[0054] In the production method of this embodiment, the size of the carbon hexagonal network plane constituting the mesophase is controlled by the gas generated from the feedstock oil composition during the coking treatment. Therefore, the residence time of the gas generated from the feedstock oil composition during the coking treatment in the system is an important control parameter for determining the size of the carbon hexagonal network plane. The residence time of the gas generated during the coking treatment in the system can be adjusted by the pressure during the coking treatment. Therefore, when the pressure in the coking treatment is within the above-mentioned preferred range, it becomes easier to limit the rate at which the gas generated from the stock oil composition is released outside the system. Furthermore, when the temperature in the coking treatment is within the above-mentioned preferred range, a better mesophase can be grown from the feed oil composition adjusted to obtain the effects of the present invention.
[0055] On the other hand, if the temperature in the coking treatment is too low and the pressure is too high, the amount of gas generated during the coking treatment becomes insufficient, and the crystal structure of the raw coke composition grows too much. In this case, it is difficult to form pores having openings on the particle surfaces of the heat-treated raw coke composition prepared by the heat treatment in step B described below, and unevenness on the particle surfaces, which is undesirable. Furthermore, if the temperature in the coking treatment is too high and the pressure is too low, an excessive amount of gas is generated during the coking treatment, and even if the material is heat-treated in the subsequent graphitization step, the graphite crystal structure is unlikely to grow, and high capacity is not achieved, making the material unsuitable as an artificial graphite material for the negative electrode of a lithium-ion secondary battery.
[0056] In the method for producing an artificial graphite material of this embodiment, the raw coke composition produced by the coking treatment is a composition containing raw coke.
[0057] [Process B] In step B, the raw coke composition produced by the coking treatment is heat-treated to obtain a heat-treated raw coke composition. Examples of the method for obtaining raw coke powder by heat treating the raw coke composition include a method of performing heat treatment under an inert gas atmosphere such as nitrogen, argon, or helium at a maximum temperature of preferably 450 to 750°C, more preferably 500 to 700°C, and even more preferably 550 to 650°C, and a holding time at the maximum temperature of preferably 0.1 to 3 hours, more preferably 0.2 to 2 hours, and even more preferably 0.5 to 1 hour. At this time, oxygen gas may be introduced into the atmospheric gas in a range of 0.01 to 21% by volume. Examples of the heating method include a method in which the raw coke composition is put into a sagger and a roller hearth kiln is used, and a method in which the raw coke composition is directly put into a rotary kiln.
[0058] The volatile content and true density of the raw coal powder in step B are correlated with the heat treatment temperature and heat treatment time of the raw coal composition. As a general trend, the higher the heat treatment temperature or the longer the heat treatment time, the smaller the volatile content of the heat-treated raw coal composition and the raw coal powder obtained therefrom, and the larger the true density. The heat treatment temperature and heat treatment time of the raw coal composition are such that the volatile content of the raw coal powder is less than 3.71% and the true density of the raw coal powder is 1.22 g / cm 3 Super 1.73g / cm 3 It must be set to be less than
[0059] The maximum temperature reached in the heat treatment of the raw coke composition is preferably 450° C. or higher, more preferably 500° C. or higher, and even more preferably 550° C. or higher, because the volatile content and true density of the raw coke powder can be easily adjusted to these ranges, the heat treatment time can be shortened, and production costs can be reduced. The maximum temperature reached in the heat treatment of the raw coke composition is preferably 750° C. or lower, more preferably 700° C. or lower, and even more preferably 650° C. or lower, because the volatile content and true density of the raw coke powder can be easily adjusted to these ranges, and the quality stability of the heat-treated raw coke composition and the raw coke powder can be improved. If the heat treatment temperature is too low, it takes a long time and the production cost increases unnecessarily, which is not preferable, whereas if the heat treatment temperature is too high, the properties (volatile content and true density) of the heat-treated raw coal composition and the raw coal powder vary widely, which is not preferable from the viewpoint of quality stability.
[0060] [Process C] In step C, the heat-treated raw coke composition produced by the heat treatment is pulverized to obtain raw coke powder. The method for obtaining the raw coke powder can be a known method such as a method using a hammer mill, and is not particularly limited.
[0061] The raw coal powder may be classified to a predetermined particle size. The average particle size of the raw coal powder is preferably 5 to 40 μm. The average particle size of the raw coal powder is based on measurement using a laser diffraction particle size distribution analyzer. When the average particle size of the raw coal powder is 40 μm or less, the artificial graphite material obtained by graphitizing the raw coal powder and then pulverizing the raw coal powder has a particle size suitable for the negative electrode of a lithium ion secondary battery. When the average particle size of the raw coal powder is 5 μm or more, the specific surface area of the artificial graphite material obtained by graphitizing the raw coal powder and then pulverizing the raw coal powder is not too large, which is preferable. If a graphite material with a too large specific surface area is used to prepare a paste-like negative electrode mixture used to form the negative electrode of a lithium ion secondary battery, the amount of solvent required is enormous, which is not preferable.
[0062] [Process D] In step D, the raw coal powder obtained by pulverizing the heat-treated raw coal composition is graphitized to obtain graphite powder. Specifically, the raw coal powder is further heat-treated to remove volatile components from the raw coal powder, and is dehydrated and pyrolyzed to cause a solid-phase graphitization reaction. By performing this graphitization process, an artificial graphite material with stable quality can be obtained.
[0063] The graphitization method may, for example, be a heat treatment in which the raw coal powder is calcined to remove volatile components to obtain calcined coke, which is then carbonized and graphitized. The calcination and carbonization may be performed as necessary, or may not be required. In the graphitization method, omission of the calcination and carbonization has almost no effect on the physical properties of the artificial graphite material finally produced.
[0064] The calcination may be carried out, for example, in an inert gas atmosphere such as nitrogen, argon, or helium at a maximum temperature of 500 to 1500° C., preferably 900 to 1200° C., for a holding time of the maximum temperature of 0 to 10 hours.
[0065] The carbonization treatment may be carried out, for example, in an inert gas atmosphere such as nitrogen, argon, or helium at a maximum temperature of 500 to 1500° C., preferably 900 to 1500° C., for a holding time of the maximum temperature of 0 to 10 hours.
[0066] The graphitization treatment may be performed, for example, by a method of performing a heat treatment in an inert gas atmosphere such as nitrogen, argon, or helium at a maximum temperature of 2500 to 3200° C., preferably 2800 to 3200° C., for a holding time at the maximum temperature of 0 to 100 hours. The graphitization treatment may be performed, for example, by sealing the raw coal powder in a crucible made of graphite and using a graphitization furnace such as an Acheson furnace or an LWG furnace.
[0067] [Process E] In step E, the method for pulverizing the graphite powder obtained by graphitizing the raw coal powder may be a known method, such as a method using an airflow jet mill, and is not particularly limited.
[0068] A lithium ion secondary battery having a negative electrode containing the artificial graphite material obtained by the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of this embodiment is resistant to deterioration in discharge capacity even when repeatedly charged and discharged at a low temperature of -10°C.
[0069] <<Negative electrodes for lithium-ion secondary batteries>> Next, the negative electrode for lithium ion secondary batteries of this embodiment will be described. The negative electrode for lithium ion secondary batteries of this embodiment includes a carbon material containing an artificial graphite material obtained by the manufacturing method of the embodiment, a binder, and a conductive assistant that is included as necessary. The negative electrode for lithium ion secondary batteries of this embodiment may include the artificial graphite material obtained by the manufacturing method of the embodiment, and may include one or more known graphite materials or amorphous carbon materials as well as the artificial graphite material obtained by the manufacturing method of the embodiment, as necessary.
[0070] Examples of known graphite materials include artificial graphite materials other than the artificial graphite material of the present embodiment, natural graphite materials, etc. Also, examples of amorphous carbon materials include known graphitizable carbon materials and non-graphitizable carbon materials.
[0071] Examples of natural graphite-based materials include graphite-like materials produced in nature, the graphite-like materials that have been highly purified and then made into spheres (including mechanochemical treatments), high-purity products or spheres whose surfaces are coated with another type of carbon (for example, pitch-coated products, CVD-coated products, etc.), and products that have been plasma-treated.
[0072] The shapes of the artificial graphite materials other than the artificial graphite material of this embodiment, the natural graphite-based materials, and the amorphous carbon materials are not particularly limited, and may be, for example, flake-like, spherical, or lump-like.
[0073] When the carbon material contains a graphite material other than the artificial graphite material obtained by the manufacturing method of the embodiment in addition to the artificial graphite material obtained by the manufacturing method of the embodiment, the mixing ratio can be any ratio. When the carbon material contains a graphite material other than the artificial graphite material obtained by the manufacturing method of the embodiment, the artificial graphite material obtained by the manufacturing method of the embodiment is preferably contained in an amount of 20 mass% or more, more preferably 30 mass% or more, and even more preferably 50 mass% or more.
[0074] As the binder, a known binder used in the negative electrode of a lithium ion secondary battery can be used, for example, carboxymethyl cellulose (CMC), polyvinylidene fluoride, polytetrafluoroethylene, SBR (styrene-butadiene rubber), etc. can be used alone or in a mixture of two or more. The content of the binder in the negative electrode mixture is preferably about 1 to 30 parts by mass per 100 parts by mass of the graphite material, and may be appropriately set according to the need in designing the lithium ion secondary battery.
[0075] The conductive assistant may be any known one used in the negative electrode of a lithium ion secondary battery, for example, carbon black, graphite, acetylene black, conductive indium-tin oxide, polyaniline, polythiophene, polyphenylene vinylene, or other conductive polymers, which may be used alone or in combination of two or more. The amount of the conductive assistant used is preferably 1 to 15 parts by mass per 100 parts by mass of the graphite material, and may be appropriately set according to the need in designing the lithium ion secondary battery.
[0076] The method for producing the negative electrode for lithium ion secondary batteries of this embodiment is not particularly limited as long as it uses a carbon material containing an artificial graphite material obtained by the manufacturing method of the embodiment, and a known manufacturing method can be used. The method for producing the negative electrode for lithium ion secondary batteries of this embodiment is to pressure mold a carbon material containing an artificial graphite material obtained by the manufacturing method of the embodiment. For example, a negative electrode mixture is produced, which is a mixture containing a carbon material containing an artificial graphite material obtained by the manufacturing method of the embodiment, a binder, a conductive assistant that is contained as necessary, and a solvent. Then, the negative electrode mixture is pressure molded to a predetermined size.
[0077] The solvent used in the negative electrode mixture may be a known solvent used in the negative electrode of a lithium ion secondary battery. Specifically, for example, organic solvents such as dimethylformamide, N-methylpyrrolidone, isopropanol, and toluene, and solvents such as water may be used alone or in combination of two or more.
[0078] When producing the negative electrode mixture, the graphite material, the binder, the conductive assistant that is contained as necessary, and the organic solvent can be mixed using a known device such as a screw type kneader, a ribbon mixer, a universal mixer, or a planetary mixer. The negative electrode mixture can be pressed using a method such as roll pressing or press pressing. The negative electrode mixture is preferably pressed at a pressure of about 100 to 300 MPa.
[0079] The negative electrode for lithium ion secondary batteries of this embodiment can be manufactured, for example, by the method shown below. That is, a graphite material containing an artificial graphite material obtained by the manufacturing method of the embodiment, a binder, a conductive assistant contained as necessary, and a solvent are kneaded by a known method to manufacture a slurry or paste-like negative electrode mixture. Then, the slurry-like negative electrode mixture is applied onto a negative electrode current collector such as copper foil, and dried to form into a shape such as a sheet or pellet. Then, the layer made of the dried negative electrode mixture is rolled and cut to a predetermined size.
[0080] The method for applying the slurry-like negative electrode mixture onto the negative electrode current collector is not particularly limited, and for example, a known method such as a metal mask printing method, an electrostatic coating method, a dip coating method, a spray coating method, a roll coating method, a doctor blade method, a gravure coating method, a screen printing method, or a die coater method can be used.
[0081] The negative electrode mixture applied onto the negative electrode current collector is preferably rolled using, for example, a flat plate press, a calendar roll, etc. The layer made of the dried negative electrode mixture formed on the negative electrode current collector can be integrated with the negative electrode current collector by a known method such as, for example, a method using a roll, a press, or a combination of these.
[0082] The material of the negative electrode current collector can be used without any particular limitation as long as it does not form an alloy with lithium. Specifically, the material of the negative electrode current collector can be, for example, copper, nickel, titanium, stainless steel, etc. The shape of the negative electrode current collector can also be used without any particular limitation. Specifically, the shape of the negative electrode current collector can be, for example, a foil, a perforated foil, a mesh, and a belt-like overall shape.
[0083] As the negative electrode current collector, for example, a porous material such as porous metal (foamed metal) or carbon paper may be used.
[0084] <<Lithium-ion secondary battery>> Next, the lithium ion secondary battery of this embodiment will be described. FIG. 1 is a schematic cross-sectional view showing an example of the lithium ion secondary battery of this embodiment. The lithium ion secondary battery 10 shown in FIG. 1 has a negative electrode 11 integrated with a negative electrode current collector 12, and a positive electrode 13 integrated with a positive electrode current collector 14. In the lithium ion secondary battery 10 shown in FIG. 1, the negative electrode of this embodiment is used as the negative electrode 11. The negative electrode 11 and the positive electrode 13 are disposed opposite to each other with a separator 15 interposed therebetween. In FIG. 1, reference numeral 16 denotes an aluminum laminate exterior. An electrolyte is injected into the aluminum laminate exterior 16.
[0085] The positive electrode 13 includes an active material, a binder, and a conductive assistant that is contained as necessary. As the active material, a known material used in a positive electrode for a lithium ion secondary battery can be used, and a metal compound, a metal oxide, a metal sulfide, or a conductive polymer material that can dope or intercalate lithium ions can be used. Specifically, as the active material, for example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganate (LiMn 2 O 4 ), and double oxides (LiCo X Ni Y Mn Z O 2, X+Y+Z=1), Lithium vanadium compound, V 2 O 5 , V 6 O 13 , V.O. 2 , MnO 2 , TiO 2 , MoV 2 O 8 , TiS 2 , V 2 S 5 , V.S. 2 , MoS 2 , MoS 3 , Cr 3 O 8 , Cr 2 O 5 , Olivine type LiMPO 4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, etc., porous carbon, etc., and mixtures thereof, etc., can be mentioned.
[0086] As the binder, it is possible to use the same binder as that used in the above-mentioned negative electrode 11. As the conductive assistant, it is possible to use the same conductive assistant as that used in the above-mentioned negative electrode 11.
[0087] For example, a valve metal or an alloy thereof that forms a passive film on the surface by anodization in an electrolyte is preferably used as the positive electrode current collector 14. Specifically, Al, Ti, Zr, Hf, Nb, Ta, and alloys containing these metals can be used. In particular, Al and its alloys are preferred because they are lightweight and have a high energy density.
[0088] For example, a nonwoven fabric, a cloth, a microporous film, or a combination thereof, mainly composed of a polyolefin such as polyethylene or polypropylene, can be used as the separator 15. If the lithium ion secondary battery has a structure in which the positive electrode and the negative electrode are not in direct contact with each other, a separator is not necessary.
[0089] Known organic electrolytic solutions, inorganic solid electrolytes, and polymer solid electrolytes used in lithium ion secondary batteries can be used as the electrolytic solution and electrolyte used in the lithium ion secondary battery 10. From the viewpoint of electrical conductivity, it is preferable to use an organic electrolytic solution as the electrolytic solution.
[0090] Examples of the organic electrolyte include ethers such as dibutyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and ethylene glycol phenyl ether; amides such as N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, and N,N-diethylacetamide; sulfur-containing compounds such as dimethylsulfoxide and sulfolane; methyl ethyl ketone, methyl isobutyl ketone, and the like. Examples of the organic electrolyte include dialkyl ketones such as tetrahydrofuran and 2-methoxytetrahydrofuran, cyclic ethers such as ethylene carbonate, butylene carbonate, propylene carbonate, and vinylene carbonate, chain carbonates such as diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, and methyl propyl carbonate, cyclic carbonates such as γ-butyrolactone and γ-valerolactone, chain carbonates such as methyl acetate, ethyl acetate, methyl propionate, and ethyl propionate, and organic solvents such as N-methyl 2-pyrrolidinone, acetonitrile, and nitromethane. These organic electrolytes can be used alone or in combination of two or more.
[0091] As the electrolyte, various known lithium salts can be used. For example, LiClO 4 , LiBF 4 , LiPF 6 , LiAlCl 4 , LiSbF 6 , LiSCN, LiCl, LiCF 3 SO 3 , LiCF 3 CO 2 , LiN(CF3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 etc.
[0092] Examples of the polymer solid electrolyte include polyethylene oxide derivatives and polymers containing said derivatives, polypropylene oxide derivatives and polymers containing said derivatives, phosphate polymers, polycarbonate derivatives and polymers containing said derivatives, and the like.
[0093] The lithium ion secondary battery 10 of this embodiment includes the negative electrode 11 containing the artificial graphite material of this embodiment, and therefore is less susceptible to capacity degradation even when subjected to repeated charge / discharge cycles at low temperatures below −10° C. For this reason, the lithium ion secondary battery 10 of this embodiment can be suitably used for automobiles such as hybrid automobiles, plug-in hybrid automobiles, and electric automobiles, and for industrial purposes such as power storage in system infrastructure.
[0094] The lithium ion secondary battery of the present invention may be any battery that uses the negative electrode of the present invention, and is not subject to any restrictions in terms of the selection of components necessary for the battery configuration other than the negative electrode.
[0095] Specifically, the structure of the lithium ion secondary battery of the present invention is not limited to the lithium ion secondary battery 10 shown in FIG.
[0096] The method for producing the lithium ion secondary battery of this embodiment is not particularly limited as long as it uses the negative electrode obtained by the method for producing a negative electrode for a lithium ion secondary battery of the embodiment, and a known production method can be used. The method for producing the lithium ion secondary battery of this embodiment includes a step of arranging the negative electrode obtained by the method for producing a negative electrode for a lithium ion secondary battery of the embodiment and a positive electrode with a separator interposed therebetween. It is preferable to include a step of integrating the negative electrode obtained by the method for producing a negative electrode for a lithium ion secondary battery of the embodiment and a negative electrode current collector, integrating the positive electrode and the positive electrode current collector, and arranging the negative electrode integrated with the negative electrode current collector and the positive electrode integrated with the positive electrode current collector with a separator interposed therebetween. A single-layer electrode body in which the negative electrode integrated with the negative electrode current collector and the positive electrode integrated with the positive electrode current collector are arranged to face each other with a separator interposed therebetween is housed in an outer casing, and an electrolyte is injected into the inside of the outer casing to obtain the lithium ion secondary battery of this embodiment.
[0097] The lithium ion secondary battery may have a structure in which, for example, a wound electrode group in which a strip-shaped positive electrode and a negative electrode are spirally wound with a separator interposed therebetween is inserted into a battery case and sealed. Alternatively, the lithium ion secondary battery may have a structure in which a stacked electrode group in which a flat-shaped positive electrode and a negative electrode are sequentially stacked with a separator interposed therebetween is enclosed in an exterior body.
[0098] The lithium ion secondary battery of the present invention can be used, for example, as a paper-type battery, a button-type battery, a coin-type battery, a laminated-type battery, a cylindrical battery, a prismatic battery, or the like. EXAMPLES
[0099] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0100] <Manufacturing of artificial graphite materials> Example 1 <Production of raw material oil composition> Atmospheric distillation residual oil is distilled under reduced pressure and then hydrodesulfurized (sulfur content 380 ppm by mass, density at 15°C 0.83 g / cm 3 ) was subjected to fluid catalytic cracking at a reaction temperature of 530°C, total pressure of 0.23MPa, catalyst / oil ratio of 13, and contact time of 7 seconds to obtain fluid catalytic cracking residue. The catalyst used was a platinum-supported silica-alumina catalyst. Note that "sulfur content" refers to the value measured according to JIS K2541.
[0101] The fluid catalytic cracking residual oil thus obtained was mixed with an equal volume of n-heptane, and then selectively extracted with dimethylformamide to separate it into aromatic and saturated fractions.
[0102] Furthermore, atmospheric distillation residual oil (sulfur content 0.35 mass%, density at 15 °C 0.92 g / cm 3 ) was distilled under reduced pressure at a furnace outlet temperature of 350°C and a pressure of 1.3kPa to obtain a vacuum distillation residual oil with an initial boiling point of 410°C, asphalt content of 9% by mass, saturates of 61% by mass, sulfur content of 0.1% by mass, and nitrogen content of 0.3% by mass. The same volume of n-heptane was added to this vacuum distillation residual oil and mixed, after which it was selectively extracted with dimethylformamide to separate it into aromatics and saturated fractions. The "nitrogen content" refers to a value measured according to JIS K2609. The "saturates" and "asphalt content" refer to values measured using a thin layer chromatograph.
[0103] The fluid catalytic cracking residual oil thus obtained, the saturated fraction of the fluid catalytic cracking residual oil, and the saturated fraction of the vacuum distillation residual oil were mixed in a mass ratio of 43:50:7 to obtain the stock oil composition of Example 1. The normal paraffin content and aromatic index fa of the obtained stock oil composition of Example 1 were determined by the methods described below. The results are shown in Table 1. In addition, the normal paraffin content and aromatic index fa of the stock oil compositions obtained in Examples 2 to 5 and Comparative Examples 4 to 8 described below were also determined by the same methods. The results are shown in Table 1.
[0104] (Normal paraffin content) The normal paraffin content of the feedstock oil composition was measured by a gas chromatograph equipped with a capillary column. Specifically, after calibration with a standard substance of normal paraffin, a sample of non-aromatic components separated by elution chromatography was passed through the capillary column and measured. The content (mass%) based on the total mass of the feedstock oil composition was calculated from the measured value.
[0105] (aromatic index fa) The aromatic index fa of the feedstock oil composition was calculated by the Knight method. 13 The spectrum of aromatic carbon by C-NMR was divided into three components (A1, A2, A3). Here, A1 is the number of carbon atoms in the aromatic ring (the number of substituted aromatic carbons and half of the unsubstituted aromatic carbons ( 13 C-NMR peak of about 40-60 ppm), and A2 is the remaining half of the unsubstituted aromatic carbon ( 13 C-NMR peak of about 60 to 80 ppm), and A3 is the number of aliphatic carbon atoms ( 13 (This corresponds to a peak at about 130 to 190 ppm in C-NMR.) The aromatic index fa was calculated using A1, A2, and A3 as fa = (A1 + A2) / (A1 + A2 + A3).
[0106] ≪Process A≫ Next, the raw oil composition of Example 1 was placed in a test tube and subjected to a heat treatment at normal pressure and 500° C. for 3 hours as a coking treatment to convert it into coke, thereby obtaining a raw coal composition of Example 1.
[0107] ≪Process B≫ The obtained raw coke composition of Example 1 was heated at 550° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition of Example 1. The heat treatment method was as follows: heating from room temperature to 550°C for 1 hour, holding at 550°C for 1 hour, and cooling from 550°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0108] ≪Process C≫ The obtained heat-treated raw coal composition of Example 1 was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining the raw coal powder of Example 1. The volatile content and true density of the obtained raw coal powder were determined by the method described below. The results are shown in Table 1. The volatile content and true density of the raw coal powders obtained in Examples 2 to 5, 9 to 13 and Comparative Examples 1 to 16 described below were also determined by the same method. The results are shown in Tables 1 and 2.
[0109] (Measurement of volatile matter) The volatile matter [mass fraction (%)] of the raw coal powder was determined in accordance with "7. Volatile matter determination method" in "7.2 Vertical tubular electric furnace method" and "b) In the case of coke" in "Coals and cokes - Methods of proximate analysis" of JIS M 8812 (2004).
[0110] (True density measurement) True density of raw coal powder [g / cm 3 ] was determined in accordance with "7.3 True density test method" in "7. Density and porosity test method" in "Cokes - Test methods" of JIS K 2151 (2004).
[0111] ≪Process D≫ The raw coal powder of Example 1 was placed in a crucible made of graphite, and the crucible was embedded in packing coke, which is a heating and heat-insulating material in an Acheson furnace, and then graphitized at 2950° C. The graphitization process consisted of heating from room temperature to 2950° C. for 130 hours, holding at 2950° C. for 8 hours, and then leaving to cool for 25 days before removing the material, to obtain graphite powder.
[0112] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 1.
[0113] (Calculation of crystallite size L(112)) The artificial graphite material for lithium ion secondary battery negative electrode of Example 1 was mixed with 10% by mass of Si standard sample as an internal standard, packed into a glass sample holder (window frame size 16 mm x 20 mm, depth 0.2 mm), and measured by wide-angle X-ray diffraction method in accordance with JIS R7651 (2007), and the crystallite size L (112) was calculated. The X-ray diffraction device used was ULTIMA IV manufactured by Rigaku Corporation, and the X-ray source was CuKα radiation (using Kβ filter Ni). The voltage and current applied to the X-ray tube were 40 kV and 40 mA.
[0114] The obtained diffraction pattern was analyzed according to a method in accordance with JIS R 7651 (2007). Specifically, the measurement data was smoothed, background was removed, and then absorption correction, polarization correction, and Lorentz correction were performed. Then, the (112) diffraction line of the artificial graphite material for the negative electrode of a lithium-ion secondary battery was corrected using the peak position and width of the (422) diffraction line of the Si standard sample, and the crystallite size L(112) was calculated. The crystallite size was calculated from the half-width of the corrected peak using the following Scherrer formula. The measurement and analysis were performed three times each, and the average value was taken as L(112).
[0115] L=K×λ / (β×cosθB) - - - - - -Scherrer's formula Where L: crystal size (nm) K: shape factor constant (=1.0) λ: wavelength of X-rays (=0.15406 nm) θ: Bragg angle (corrected diffraction angle) β: True half-width (corrected value)
[0116] (Measurement of nitrogen adsorption specific surface area S(BET)) The nitrogen adsorption specific surface area of the artificial graphite material for the negative electrode of a lithium ion secondary battery in Example 1 was measured and calculated using a specific surface area measuring device (BELSORPminiII) manufactured by Microtrack-Bell Corporation in accordance with JIS Z 8830 (2013) "Method for measuring the specific surface area of powder (solid) by gas adsorption." The artificial graphite material was pre-dried under reduced pressure at 300°C for 3 hours. Thereafter, the specific surface area value (m 2 / g) was calculated.
[0117] (Measurement of ESR signal intensity I(4.8K) and calculation of I(4.8K) / S(BET)) About 1.5 mg of the artificial graphite material for the negative electrode of the lithium ion secondary battery of Example 1 was placed in a sample tube, and after evacuation with a rotary pump, He gas was sealed in the sample tube and ESR measurement was performed. The ESR device, microwave frequency counter, Gauss meter, and cryostat used were ESP350E manufactured by BRUKER, HP5351P manufactured by HEWLETT PACKARD, ER035M manufactured by BRUKER, and ESR910 manufactured by OXFORD, respectively. The microwave used was X-band (9.60 GHz), and the measurement was performed under the conditions of intensity 1 mW, central magnetic field 3412 G, and magnetic field modulation 100 kHz. The measurement temperature was 4.8 K, and the absorption intensity (I4.8 K) was calculated and shown in Table 1. The signal intensity is a value (spins / g) obtained by integrating the ESR spectrum twice and correcting it with a standard substance. It was confirmed that the peak derived from carbon radicals, which appears in the electron spin resonance method measured using microwaves in the X-band region, appears near g=2.0 in the negative electrode materials of all the Examples and Comparative Examples. The value of the ratio I(4.8K) / S(BET) of the obtained signal intensity I(4.8K) to the nitrogen adsorption specific surface area S(BET) (spins / m 2 ) was calculated.
[0118] The crystallite size L(112), nitrogen adsorption specific surface area S(BET), ESR signal intensity I(4.8K) at a temperature of 4.8K, and ratio I(4.8K) / S(BET) of the obtained artificial graphite material for lithium ion secondary battery negative electrode are shown in Table 1. The crystallite size L(112), nitrogen adsorption specific surface area S(BET), ESR signal intensity I(4.8K) at a temperature of 4.8K, and ratio I(4.8K) / S(BET) of the artificial graphite material for lithium ion secondary battery negative electrode of Examples 2 to 5 and Comparative Examples 1 to 8 were also determined in the same manner. The results are shown in Table 1.
[0119] Example 2 <Production of raw material oil composition> Atmospheric distillation residual oil with a sulfur content of 3.1% by mass was hydrodesulfurized in the presence of a catalyst so that the hydrocracking rate was 25% or less to obtain a hydrodesulfurized oil. The hydrodesulfurization conditions were a total pressure of 18 MPa, a hydrogen partial pressure of 16 MPa, and a temperature of 380°C.
[0120] The hydrodesulfurized oil thus obtained and the fluid catalytic cracking residual oil obtained in Example 1 were mixed in a mass ratio of 5:95 to obtain a stock oil composition of Example 2.
[0121] ≪Process A≫ The raw oil composition of Example 2 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0122] ≪Process B≫ The obtained raw coke composition was heated at 700° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 700°C for 2 hours, holding at 700°C for 1 hour, and cooling from 700°C to 400°C for 2 hours. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0123] ≪Process C≫ The obtained heat-treated raw coke composition was pulverized in a hammer mill so that the average particle size, as measured by a laser diffraction particle size distribution analyzer, was in the range of 19.5 to 20.5 μm, thereby obtaining raw coke powder of Example 2.
[0124] ≪Process D≫ The raw coal powder of Example 2 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0125] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 2.
[0126] Example 3 <Production of raw material oil composition> The saturated fraction of the fluid catalytic cracking residue obtained in Example 1 and the aromatic fraction of the fluid catalytic cracking residue were mixed in a mass ratio of 70:30 to obtain a stock oil composition of Example 3.
[0127] ≪Process A≫ The raw oil composition of Example 3 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0128] ≪Process B≫ The obtained raw coke composition was heated to 600°C under a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: the temperature was increased from room temperature to 600°C for 1 hour and 30 minutes, the temperature was held at 600°C for 1 hour, the temperature was decreased from 600°C to 400°C for 1 hour and 30 minutes, and after 400°C, the temperature was allowed to cool for 4 hours while continuing the nitrogen gas flow.
[0129] ≪Process C≫ The obtained heat-treated raw coke composition was pulverized in a hammer mill so that the average particle size, as measured by a laser diffraction particle size distribution analyzer, was in the range of 19.5 to 20.5 μm, thereby obtaining raw coke powder of Example 3.
[0130] ≪Process D≫ The raw coal powder of Example 3 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0131] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 3.
[0132] Example 4 <Production of raw material oil composition> The saturated fraction of the vacuum distillation residual oil obtained in Example 1 and the aromatic fraction of the fluid catalytic cracking residual oil also obtained in Example 1 were mixed in a mass ratio of 30:70 to obtain the raw material oil composition of Example 4.
[0133] ≪Process A≫ The raw oil composition of Example 4 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0134] ≪Process B≫ The obtained raw coke composition was heated at 500° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 500°C for 1 hour, holding at 500°C for 1 hour, and cooling from 500°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0135] ≪Process C≫ The obtained heat-treated raw coke composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coke powder of Example 4.
[0136] ≪Process D≫ The raw coal powder of Example 4 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0137] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 4.
[0138] Example 5 <Production of raw material oil composition> The saturated fraction of the fluid catalytic cracking residual oil obtained in Example 1, the aromatic fraction of the fluid catalytic cracking residual oil also obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 20:20:60 to obtain the feedstock oil composition of Example 5.
[0139] ≪Process A≫ The raw oil composition of Example 5 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0140] ≪Process B≫ The obtained raw coke composition was heated at 500° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 500°C for 1 hour, holding at 500°C for 1 hour, and cooling from 500°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0141] ≪Process C≫ The obtained heat-treated raw coke composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coke powder of Example 5.
[0142] ≪Process D≫ The raw coal powder of Example 5 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0143] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 5.
[0144] Comparative Example 1 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 1.
[0145] <Low temperature heat treatment process> The raw coke composition of Example 1 was heated at 400° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition of Comparative Example 1. The heat treatment method consisted of increasing the temperature from room temperature to 400° C. for 1 hour, maintaining the temperature at 400° C. for 1 hour, and then allowing the material to cool for 4 hours while continuing the nitrogen gas flow.
[0146] ≪Process C≫ The obtained heat-treated raw coke composition of Comparative Example 1 was pulverized in a hammer mill so that the average particle size, as measured by a laser diffraction particle size distribution analyzer, was in the range of 19.5 to 20.5 μm, to obtain raw coke powder.
[0147] ≪Process D≫ The raw coal powder of Comparative Example 1 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0148] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 1.
[0149] Comparative Example 2 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 1.
[0150] <High-temperature heat treatment process> The raw coke composition of Example 1 was heated at 750° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition of Comparative Example 2. The heat treatment method was as follows: the temperature was increased from room temperature to 750°C for 2 hours, held at 750°C for 1 hour, and decreased from 750°C to 400°C for 2 hours. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow. After that, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0151] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 2 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coal powder of Comparative Example 2.
[0152] ≪Process D≫ The raw coal powder of Comparative Example 2 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0153] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 2.
[0154] Comparative Example 3 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 1.
[0155] <Heat treatment process> In the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 3, the raw coke composition was not subjected to a heat treatment.
[0156] ≪Process C≫ The raw coke composition of Example 1 was pulverized with a hammer mill so that the average particle size measured with a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, to obtain raw coke powder.
[0157] ≪Process D≫ The raw coal powder thus obtained was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0158] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 3.
[0159] Comparative Example 4 <Production of raw material oil composition> The aromatic fraction of the fluid catalytic cracking residual oil obtained in Example 1, the saturated fraction of the fluid catalytic cracking residual oil also obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 15:20:65 to obtain the raw material oil composition of Comparative Example 4.
[0160] ≪Process A≫ The raw oil composition of Comparative Example 4 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0161] ≪Process B≫ The obtained raw coke composition was heated at 500° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 500°C for 1 hour, holding at 500°C for 1 hour, and cooling from 500°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0162] ≪Process C≫ The obtained heat-treated raw coal composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coal powder of Comparative Example 4.
[0163] ≪Process D≫ The raw coal powder of Comparative Example 4 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0164] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 4.
[0165] Comparative Example 5 <Production of raw material oil composition> The aromatic fraction of the fluid catalytic cracking residue obtained in Example 1 and the saturated fraction of the fluid catalytic cracking residue also obtained in Example 1 were mixed in a mass ratio of 50:50 to obtain a raw material oil composition of Comparative Example 5.
[0166] ≪Process A≫ The raw oil composition of Comparative Example 5 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0167] ≪Process B≫ The obtained raw coke composition was heated at 700° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 700°C for 2 hours, holding at 700°C for 1 hour, and cooling from 700°C to 400°C for 2 hours. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0168] ≪Process C≫ The obtained heat-treated raw coal composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coal powder of Comparative Example 5.
[0169] ≪Process D≫ The raw coal powder of Comparative Example 5 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0170] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 5.
[0171] Comparative Example 6 <Production of raw material oil composition> The saturated fraction of the vacuum distillation residual oil obtained in Example 1 and the aromatic fraction of the fluid catalytic cracking residual oil also obtained in Example 1 were mixed in a mass ratio of 15:85 to obtain the raw material oil composition of Comparative Example 6.
[0172] ≪Process A≫ The raw oil composition of Comparative Example 6 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0173] ≪Process B≫ The obtained raw coke composition was heated at 600° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 600°C in 1 hour and 30 minutes, holding at 600°C for 1 hour, and cooling from 600°C to 400°C in 1 hour and 30 minutes. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0174] ≪Process C≫ The obtained heat-treated raw coal composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coal powder of Comparative Example 6.
[0175] ≪Process D≫ The raw coal powder of Comparative Example 6 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0176] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 6.
[0177] Comparative Example 7 <Production of raw material oil composition> The saturated fraction of the vacuum distillation residual oil obtained in Example 1, the aromatic fraction of the fluid catalytic cracking residual oil also obtained in Example 1, and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 4:91:5 to obtain the raw material oil composition of Comparative Example 7.
[0178] ≪Process A≫ The raw oil composition of Comparative Example 7 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0179] ≪Process B≫ The obtained raw coke composition was heated at 650° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 650°C in 1 hour and 30 minutes, holding at 650°C for 1 hour, and cooling from 650°C to 400°C in 1 hour and 30 minutes. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0180] ≪Process C≫ The obtained heat-treated raw coal composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coal powder of Comparative Example 7.
[0181] ≪Process D≫ The raw coal powder of Comparative Example 7 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0182] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 7.
[0183] Comparative Example 8 <Production of raw material oil composition> The aromatic content of the fluid catalytic cracking residual oil obtained in Example 1 and the hydrodesulfurized oil obtained in Example 2 were mixed in a mass ratio of 15:85 to obtain a stock oil composition of Comparative Example 8.
[0184] ≪Process A≫ The raw oil composition of Comparative Example 8 was coked by the same coking treatment as in Example 1 to obtain a raw coal composition.
[0185] ≪Process B≫ The obtained raw coke composition was heated at 550° C. in a nitrogen gas flow to obtain a heat-treated raw coke composition. The heat treatment method was as follows: heating from room temperature to 550°C for 1 hour, holding at 550°C for 1 hour, and cooling from 550°C to 400°C for 1 hour. After 400°C, the material was left to cool for 4 hours while continuing the nitrogen gas flow.
[0186] ≪Process C≫ The obtained heat-treated raw coal composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 19.5 to 20.5 μm, thereby obtaining raw coal powder of Comparative Example 8.
[0187] ≪Process D≫ The raw coal powder of Comparative Example 8 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0188] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 9.5 to 10.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 8.
[0189] Example 6 The artificial graphite material obtained in Example 1 and the artificial graphite material obtained in Comparative Example 3 were mixed in a mass ratio of 50:50 to obtain an artificial graphite material for a lithium ion secondary battery negative electrode of Example 6.
[0190] Example 7 An artificial graphite material for a lithium ion secondary battery negative electrode of Example 7 was obtained by mixing the artificial graphite material obtained in Example 1 and the artificial graphite material obtained in Comparative Example 3 in a mass ratio of 30:70.
[0191] Example 8 An artificial graphite material for a lithium ion secondary battery negative electrode of Example 8 was obtained, which was a mixture of the artificial graphite material obtained in Example 1 and the artificial graphite material obtained in Comparative Example 3 in a mass ratio of 20:80.
[0192] <Preparation of evaluation battery (1)> 1 was fabricated as an evaluation battery by the method described below. The negative electrode 11, negative electrode current collector 12, positive electrode 13, positive electrode current collector 14, and separator 15 used were as follows.
[0193] (Negative electrode 11, negative electrode current collector 12) Any of the artificial graphite materials obtained in Examples 1 to 8 and Comparative Examples 1 to 8, an aqueous solution of carboxymethyl cellulose (CMC (BSH-6 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.)) as a binder adjusted to a concentration of 1.5 mass%, and an aqueous solution in which styrene-butadiene rubber (SBR) as a binder was dispersed at a concentration of 48 mass% were mixed in a solid mass ratio of 98:1:1 to obtain a paste-like negative electrode mixture. The obtained negative electrode mixture was applied to the entire surface of one side of a copper foil having a thickness of 18 μm as a negative electrode current collector 12, and then dried and rolled to obtain a negative electrode sheet in which a negative electrode 11, which is a layer made of the negative electrode mixture, was formed on the negative electrode current collector 12. The amount of the negative electrode mixture applied per unit area on the negative electrode sheet is approximately 9.4 mg / cm2 in terms of the mass of the graphite material. 2 It was adjusted so that
[0194] Thereafter, the negative electrode sheet was cut to a width of 32 mm and a length of 52 mm. A part of the negative electrode 11 was then scraped off in a direction perpendicular to the longitudinal direction of the sheet to expose the negative electrode current collector 12 that served as a negative electrode lead plate.
[0195] (Positive electrode 13, positive electrode current collector 14) The positive electrode material is lithium cobalt oxide LiCoO with an average particle size of 10 μm. 2 A positive electrode mixture paste was obtained by mixing polyvinylidene fluoride (Cellseed (registered trademark) C10N manufactured by Nippon Chemical Industry Co., Ltd.) as a binder (KF#1120 manufactured by Kureha Corporation) and acetylene black (Denka Black (registered trademark) manufactured by Denka Co., Ltd.) as a conductive additive in a mass ratio of 89:6:5, adding N-methyl-2-pyrrolidinone as a solvent and kneading the mixture. The obtained positive electrode mixture was applied to the entire surface of one side of an aluminum foil having a thickness of 30 μm as a positive electrode current collector 14, and then dried and rolled to obtain a positive electrode sheet in which a positive electrode 13, which is a layer made of the positive electrode mixture, was formed on the positive electrode current collector 14. The amount of the positive electrode mixture applied per unit area on the positive electrode sheet is approximately 20 mg / cm2 as the mass of lithium cobalt oxide. 2 It was adjusted so that
[0196] Thereafter, the positive electrode sheet was cut to a width of 30 mm and a length of 50 mm. A part of the positive electrode 13 was then scraped off in a direction perpendicular to the longitudinal direction of the sheet to expose the positive electrode current collector 14 that served as a positive electrode lead plate.
[0197] (Separator 15) As the separator 15, a cellulose-based nonwoven fabric (TF40-50 manufactured by Nippon Koshi Co., Ltd.) was used. In order to prepare the lithium-ion secondary battery 10 shown in FIG. 1, first, a negative electrode sheet in which the negative electrode 11, the negative electrode current collector 12, and the negative electrode lead plate are integrated, a positive electrode sheet in which the positive electrode 13, the positive electrode current collector 14, and the positive electrode lead plate are integrated, the separator 15, and other members used in the lithium-ion secondary battery 10 were dried. Specifically, the negative electrode sheet and the positive electrode sheet were dried at 120° C. under reduced pressure for 12 hours or more. In addition, the separator 15 and other members were dried at 70° C. under reduced pressure for 12 hours or more.
[0198] Next, the dried negative electrode sheet, positive electrode sheet, separator 15, and other members were assembled in an argon gas circulating glove box in which the dew point was controlled to -60°C or less. As a result, a single-layer electrode body was obtained in which the positive electrode 13 and the negative electrode 11 were laminated facing each other with the separator 15 interposed therebetween, and fixed with polyimide tape (not shown), as shown in Figure 1. The negative electrode sheet and the positive electrode sheet were laminated such that the peripheral portion of the laminated positive electrode sheet was surrounded by the inner peripheral portion of the negative electrode sheet.
[0199] Next, the single-layer electrode body was housed in an aluminum laminate exterior 16, and an electrolytic solution was poured into the interior. The electrolytic solution was a solvent containing lithium hexafluorophosphate (LiPF 6 ) was dissolved to a concentration of 1 mol / L, and vinylene carbonate (VC) was further mixed to a concentration of 1 mass %. As the solvent, a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 was used.
[0200] Thereafter, with the positive electrode lead plate and the negative electrode lead plate protruding, the aluminum laminate exterior 16 was heat-sealed. By the above steps, the sealed lithium ion secondary batteries 10 of Examples 1 to 8 and Comparative Examples 1 to 8 were obtained.
[0201] <Charge and discharge test of evaluation battery (1)> The lithium ion secondary batteries 10 of Examples 1 to 8 and Comparative Examples 1 to 8 were subjected to the following charge / discharge tests. First, a preliminary test was conducted to detect abnormalities in the battery. That is, the battery was placed in a constant temperature room at 25°C, and charged at a constant current of 4 mA until the battery voltage reached 4.2 V, and after a 10-minute pause, it was discharged at the same constant current until the battery voltage reached 3.0 V. This cycle of charging, pausing, and discharging was considered as one charge-discharge cycle, and the charge-discharge cycle was repeated three times under the same conditions to perform the preliminary test. This preliminary test confirmed that there were no abnormalities in all of the batteries of Examples 1 to 8 and Comparative Examples 1 to 8. Then, the main test described below was carried out. Note that the preliminary test is not included in the number of cycles in the main test.
[0202] In this test, the battery was placed in a constant temperature room at 25°C and subjected to constant current / constant voltage charging with a charging current of 30 mA, charging voltage of 4.2 V, and charging time of 3 hours, followed by a 10-minute pause and then constant current discharge at the same current (30 mA) until the battery voltage reached 3.0 V. This cycle of charging, pausing, and discharging constituted one charge / discharge cycle, and the charge / discharge cycle was repeated three times under the same conditions, with the discharge capacity in the third cycle being designated the "initial discharge capacity."
[0203] Next, the battery was placed in a thermostatic chamber set at -10°C and left for 5 hours, after which the charge / discharge cycle was repeated 100 times under the same conditions as the charge / discharge cycle for determining the initial discharge capacity.The battery was then placed again in a thermostatic chamber at 25°C and left for 5 hours, after which the charge / discharge cycle was repeated three times under the same conditions as the charge / discharge cycle for determining the initial discharge capacity, and the discharge capacity of the third cycle was recorded as the "discharge capacity after repeated charge / discharge at -10°C."
[0204] As an index showing the capacity deterioration after repeated charging and discharging at -10°C, the retention rate (%) of the "discharge capacity after repeated charging and discharging at -10°C" to the above "initial discharge capacity" was calculated using the following (Equation 1). The results are shown in Table 1.
[0205]
number
[0206] [Table 1]
[0207] As shown in Table 1, the negative electrodes of the lithium ion secondary batteries of Examples 1 to 8 had a volatile content of less than 3.71% and a true density of 1.22 g / cm 3 Super 1.73g / cm 3 The artificial graphite material obtained by the manufacturing method of the present invention is used by using heat-treated raw coal powder having a carbon content of less than 100%. In the lithium ion secondary batteries of Examples 1 to 8, the "discharge capacity retention rate (%) after repeated charging and discharging at -10°C" was 67% or more. This confirmed that the lithium ion secondary batteries using the negative electrodes containing the artificial graphite material obtained by the production method of the present invention are unlikely to deteriorate in discharge capacity even when the charge and discharge cycles are repeated at a temperature of -10°C.
[0208] Furthermore, as shown in Table 1, the lithium ion secondary batteries of Examples 1 to 8 had a "discharge capacity retention rate after repeated charging and discharging at -10°C" of 67.5% or more. This confirmed that the lithium ion secondary batteries using negative electrodes containing the artificial graphite material for lithium ion secondary battery negative electrodes of Examples 1 to 8 were less susceptible to deterioration in discharge capacity even when rapid charging was repeated.
[0209] On the other hand, for the negative electrode of the lithium ion secondary battery of Comparative Example 1, an artificial graphite material obtained by using heat-treated raw coal powder whose volatile content is outside the range of less than 3.71% is used. The negative electrodes of the lithium ion secondary batteries of Comparative Examples 4, 5, and 6 had a true density of 1.22 g / cm 3 Super 1.73g / cm 3 In the past, artificial graphite materials have been used that are obtained using heat-treated raw coal powder that is outside the above range. The negative electrodes of the lithium ion secondary batteries of Comparative Examples 2, 7, and 8 had a volatile content outside the range of less than 3.71% and a true density of 1.22 g / cm 3 Super 1.73g / cm 3 In the past, artificial graphite materials have been used that are obtained using heat-treated raw coal powder that is outside the above range. The negative electrode of the lithium ion secondary battery of Comparative Example 3 uses an artificial graphite material obtained by using raw coal powder that has not been heat-treated and has a volatile content outside the range of less than 3.71%.
[0210] In all of the lithium ion secondary batteries of Comparative Examples 1 to 8, the "discharge capacity retention rate (%) after repeated charging and discharging at -10°C" was less than 46%, and it was confirmed that the discharge capacity was prone to deterioration compared to Examples 1 to 8.
[0211] Example 9 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 1.
[0212] ≪Process B≫ A heat-treated raw coke composition of Example 9 was obtained in the same manner as in Example 1, except that a mixed gas of nitrogen and oxygen with a volume ratio of 83:17 was used instead of the nitrogen gas in Example 1.
[0213] ≪Process C≫ The obtained heat-treated raw coal composition of Example 9 was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 20.5 to 21.5 μm, thereby obtaining the raw coal powder of Example 9.
[0214] ≪Process D≫ The raw coal powder of Example 9 was placed in a crucible made of graphite, and the crucible was embedded in packing coke, which is a heating and heat-insulating material in an Acheson furnace, and then graphitized at 2950° C. The graphitization process consisted of heating from room temperature to 2950° C. for 130 hours, holding at 2950° C. for 8 hours, and then leaving to cool for 25 days before removing the material, to obtain graphite powder.
[0215] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 14.5 to 15.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 9.
[0216] Example 10 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 2.
[0217] ≪Process B≫ The heat-treated raw coal composition of Example 10 was obtained in the same manner as in Example 2, except that a mixed gas of nitrogen and oxygen with a volume ratio of 98:2 was used instead of the nitrogen gas in Example 2.
[0218] ≪Process C≫ The obtained heat-treated raw coal composition of Example 10 was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 14.5 to 15.5 μm, thereby obtaining the raw coal powder of Example 10.
[0219] ≪Process D≫ The raw coal powder of Example 10 was graphitized in the same manner as in Example 1 to obtain graphite powder.
[0220] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 11.5 to 12.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 10.
[0221] Example 11 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 3.
[0222] ≪Process B≫ A heat-treated raw coal composition of Example 11 was obtained in the same manner as in Example 3, except that a mixed gas of nitrogen and oxygen with a volume ratio of 90:10 was used instead of the nitrogen gas.
[0223] ≪Process C≫ The obtained heat-treated raw coal composition of Example 11 was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 12.5 to 13.5 μm, thereby obtaining the raw coal powder of Example 11.
[0224] ≪Process D≫ The raw coal powder of Example 11 was placed in a graphite crucible and graphitized at 2850°C under a nitrogen gas flow using a high-frequency induction furnace. The graphitization process consisted of heating from room temperature to 2850°C for 23 hours, holding the temperature at 2850°C for 3 hours, and then allowing the powder to cool for 6 days before being removed, to obtain graphite powder.
[0225] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 8.5 to 9.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 11.
[0226] Example 12 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 4.
[0227] ≪Process B≫ A heat-treated raw coal composition of Example 12 was obtained in the same manner as in Example 4, except that a mixed gas of nitrogen and oxygen with a volume ratio of 83:17 was used instead of the nitrogen gas in Example 4.
[0228] ≪Process C≫ The obtained heat-treated raw coal composition of Example 12 was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 20.5 to 21.5 μm, thereby obtaining the raw coal powder of Example 12.
[0229] ≪Process D≫ The raw coal powder of Example 12 was placed in a graphite crucible and graphitized at 2850°C under a nitrogen gas flow using a high-frequency induction furnace. The graphitization process consisted of heating from room temperature to 2850°C for 23 hours, holding at 2850°C for 3 hours, and allowing to cool for 6 days before removing the material, to obtain graphite powder.
[0230] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 10.5 to 11.5 μm, thereby obtaining the artificial graphite material for lithium ion secondary battery negative electrodes of Example 12.
[0231] Example 13 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 5.
[0232] ≪Process B≫ A heat-treated raw coal composition of Example 13 was obtained in the same manner as in Example 3, except that in Example 5, a mixed gas of nitrogen and oxygen with a volume ratio of 83:17 was used instead of the nitrogen gas.
[0233] ≪Process C≫ The obtained heat-treated raw coke composition was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 20.5 to 21.5 μm, thereby obtaining the raw coke powder of Example 13.
[0234] ≪Process D and Process E≫ An artificial graphite material for a lithium ion secondary battery negative electrode of Example 13 was obtained in the same manner as in Example 12, except that the raw coal powder of Example 13 was used instead of the raw coal powder of Example 12, and the raw coal powder was pulverized with an air flow jet mill so that the average particle size was in the range of 8.5 to 9.5 μm.
[0235] Comparative Example 9 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 1.
[0236] <Low temperature heat treatment process> A heat-treated raw coal composition of Comparative Example 9 was obtained in the same manner as in Comparative Example 1, except that a mixed gas of nitrogen and oxygen with a volume ratio of 83:17 was used instead of the nitrogen gas in Comparative Example 1.
[0237] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 9 was pulverized in a hammer mill so that the average particle size measured by a laser diffraction particle size distribution analyzer was in the range of 17.5 to 18.5 μm, thereby obtaining raw coal powder of Comparative Example 9.
[0238] ≪Process D and Process E≫ An artificial graphite material for a lithium-ion secondary battery negative electrode of Comparative Example 9 was obtained in the same manner as in Example 12, except that the raw coal powder of Comparative Example 9 was used instead of the raw coal powder of Example 12, and that the raw coal powder was pulverized using an air flow jet mill so that the average particle size was in the range of 14.5 to 15.5 μm.
[0239] Comparative Example 10 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 1.
[0240] <High-temperature heat treatment process> In Comparative Example 2, the nitrogen gas was replaced with a mixed gas flow of nitrogen and oxygen having a volume ratio of 99:1, and heating was performed at 750° C. to obtain a heat-treated raw coal composition of Comparative Example 10.
[0241] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 10 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 20.5 to 21.5 μm, thereby obtaining the raw coal powder of Comparative Example 10.
[0242] ≪Process D and Process E≫ An artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 10 was obtained in the same manner as in Example 12, except that the raw coal powder of Comparative Example 10 was used instead of the raw coal powder of Example 12.
[0243] Comparative Example 11 ≪Process A≫ A raw coke composition was obtained in the same manner as in Example 1.
[0244] <Heat treatment process> In the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 11, the raw coke composition was not subjected to a heat treatment.
[0245] ≪Process C≫ The raw coke composition of Example 1 was pulverized with a hammer mill so that the average particle size measured with a laser diffraction particle size distribution analyzer was in the range of 17.5 to 18.5 μm, to obtain raw coke powder.
[0246] ≪Process D≫ The raw coal powder of Comparative Example 11 thus obtained was graphitized in the same manner as in Example 9 to obtain graphite powder.
[0247] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 12.5 to 13.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 11.
[0248] Comparative Example 12 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 4.
[0249] ≪Process B≫ A heat-treated raw coal composition of Comparative Example 12 was obtained in the same manner as in Comparative Example 4, except that a mixed gas of nitrogen and oxygen with a volume ratio of 83:17 was used instead of the nitrogen gas in Comparative Example 4.
[0250] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 12 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 15.5 to 16.5 μm, thereby obtaining the raw coal powder of Comparative Example 12.
[0251] ≪Process D and Process E≫ An artificial graphite material for a lithium ion secondary battery negative electrode of Comparative Example 12 was obtained in the same manner as in Example 12, except that the raw coal powder of Comparative Example 12 was used instead of the raw coal powder of Example 12, and that the raw coal powder was pulverized using an air flow jet mill so that the average particle size was in the range of 13.5 to 14.5 μm.
[0252] Comparative Example 13 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 5.
[0253] ≪Process B≫ A heat-treated raw coal composition of Comparative Example 13 was obtained in the same manner as in Comparative Example 5, except that a mixed gas of nitrogen and oxygen with a volume ratio of 98:2 was used instead of the nitrogen gas in Comparative Example 5.
[0254] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 13 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 20.5 to 21.5 μm, thereby obtaining the raw coal powder of Comparative Example 13.
[0255] ≪Process D≫ The raw coal powder of Comparative Example 13 was placed in a graphite crucible and graphitized at 2850°C under a nitrogen gas flow using a high-frequency induction furnace. The graphitization treatment consisted of heating from room temperature to 2850°C for 23 hours, holding at 2850°C for 3 hours, and then allowing to cool for 6 days before removing the material, to obtain graphite powder.
[0256] ≪Process E≫ The obtained graphite powder was pulverized in an air flow jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 7.5 to 8.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 13.
[0257] Comparative Example 14 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 6.
[0258] ≪Process B≫ A heat-treated raw coal composition of Comparative Example 14 was obtained in the same manner as in Comparative Example 6, except that a mixed gas of nitrogen and oxygen with a volume ratio of 90:10 was used instead of the nitrogen gas in Comparative Example 6.
[0259] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 14 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 18.5 to 19.5 μm, thereby obtaining the raw coal powder of Comparative Example 14.
[0260] ≪Process D≫ The raw coal powder of Comparative Example 14 was graphitized in the same manner as in Example 9 to obtain graphite powder.
[0261] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 7.5 to 8.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 14.
[0262] Comparative Example 15 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 7.
[0263] ≪Process B≫ A heat-treated raw coal composition of Comparative Example 15 was obtained in the same manner as in Comparative Example 7, except that a mixed gas of nitrogen and oxygen with a volume ratio of 94:6 was used instead of the nitrogen gas in Comparative Example 7.
[0264] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 15 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 20.5 to 21.5 μm, thereby obtaining the raw coal powder of Comparative Example 15.
[0265] ≪Process D≫ The raw coal powder of Comparative Example 15 was graphitized in the same manner as in Example 9 to obtain graphite powder.
[0266] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 11.5 to 12.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 15.
[0267] Comparative Example 16 ≪Process A≫ A raw coke composition was obtained in the same manner as in Comparative Example 8.
[0268] ≪Process B≫ A heat-treated raw coal composition of Comparative Example 16 was obtained in the same manner as in Comparative Example 8, except that a mixed gas of nitrogen and oxygen with a volume ratio of 83:17 was used instead of the nitrogen gas in Comparative Example 8.
[0269] ≪Process C≫ The obtained heat-treated raw coal composition of Comparative Example 16 was pulverized in a hammer mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 17.5 to 18.5 μm, thereby obtaining the raw coal powder of Comparative Example 16.
[0270] ≪Process D≫ The raw coal powder of Comparative Example 16 was placed in a graphite crucible and graphitized at 2850°C under a nitrogen gas flow using a high-frequency induction furnace. The graphitization treatment consisted of heating from room temperature to 2850°C for 23 hours, holding at 2850°C for 3 hours, and allowing to cool for 6 days before removing the powder, to obtain graphite powder.
[0271] ≪Process E≫ The obtained graphite powder was pulverized in an air jet mill so that the average particle diameter measured by a laser diffraction particle size distribution analyzer was in the range of 10.5 to 11.5 μm, thereby obtaining an artificial graphite material for lithium ion secondary battery negative electrodes of Comparative Example 16.
[0272] Example 14 The artificial graphite material obtained in Example 9 and the artificial graphite material obtained in Comparative Example 11 were mixed in a mass ratio of 50:50 to obtain an artificial graphite material for a lithium ion secondary battery negative electrode of Example 14.
[0273] Example 15 An artificial graphite material for a lithium ion secondary battery negative electrode of Example 15 was obtained by mixing the artificial graphite material obtained in Example 9 and the artificial graphite material obtained in Comparative Example 11 in a mass ratio of 30:70.
[0274] Example 16 An artificial graphite material for a lithium ion secondary battery negative electrode of Example 16 was obtained by mixing the artificial graphite material obtained in Example 9 and the artificial graphite material obtained in Comparative Example 11 in a mass ratio of 20:80.
[0275] For the artificial graphite materials for lithium ion secondary battery negative electrodes of Examples 9 to 13 and Comparative Examples 9 to 16, the crystallite size L(112), nitrogen adsorption specific surface area S(BET), ESR signal intensity I(4.8K) at a temperature of 4.8K, and ratio I(4.8K) / S(BET) were determined in the same manner as in Example 1. The results are shown in Table 2.
[0276] <Preparation of evaluation battery (2)> Instead of any of the artificial graphite materials obtained in Examples 1 to 8 and Comparative Examples 1 to 8, any of the artificial graphite materials obtained in Examples 9 to 16 and Comparative Examples 9 to 16 were used, and lithium cobalt oxide LiCoO having an average particle size of 10 μm was used as the positive electrode material. 2 The composite oxide of nickel, cobalt, manganese and lithium, NCM523 (manufactured by Beijing Easpring Material Technology Co., Ltd.), with an average particle size of 12 μm, was used instead of the positive electrode sheet. The amount of the positive electrode mixture applied per unit area on the positive electrode sheet was approximately 17.2 mg / cm2 in terms of the mass of NCM523. 2 Sealed lithium ion secondary batteries 10 of Examples 9 to 16 and Comparative Examples 9 to 16 were obtained in the same manner as in the above “Preparation of evaluation battery (1)”, except that the electrolyte solvent was changed from a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 to a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3.
[0277] <Charge and discharge test of evaluation battery (2)> The lithium ion secondary batteries 10 of Examples 9 to 16 and Comparative Examples 9 to 16 were evaluated in the same manner as in the above-mentioned "Charge and discharge test (1) of evaluation battery." The results are shown in Table 2.
[0278] [Table 2]
[0279] As shown in Table 2, the negative electrodes of the lithium ion secondary batteries of Examples 9 to 16 have a crystallite size L(112) of 4 to 30 nm calculated from the (112) diffraction line measured by wide-angle X-ray diffraction, and a nitrogen adsorption specific surface area S(BET) of 2.5 to 6.2 m 2 / g, and in the electron spin resonance method measured using X-band, the absorption spectrum originating from carbon radicals appears at around g = 2.0. The ratio I(4.8K) / S(BET) of the spin density I(4.8K)(spins / g) calculated from the signal intensity at a temperature of 4.8K to S(BET) is 5.2 × 10 17 ~6.8×10 17 spins / m 2 The negative electrode is made of an artificial graphite material having a volatile content of less than 3.71% and a true density of 1.22 g / cm 3 Super 1.73g / cm 3 The artificial graphite material obtained by the manufacturing method of the present invention is used by using heat-treated raw coal powder having a carbon content of less than 100%. In the lithium ion secondary batteries of Examples 9 to 16, the "discharge capacity retention rate (%) after repeated charge and discharge at -10°C" was 75% or more. This confirmed that the discharge capacity of the lithium ion secondary batteries using the negative electrodes containing the artificial graphite material of the present invention and the artificial graphite material obtained by the production method of the present invention is unlikely to deteriorate even when the charge and discharge cycles are repeated at a temperature of -10°C.
[0280] Furthermore, as shown in Table 2, the lithium ion secondary batteries of Examples 9 to 16 had a "discharge capacity retention rate after repeated charging and discharging at -10°C" of 75.5% or more. This confirmed that the lithium ion secondary batteries using the negative electrodes containing the artificial graphite materials for lithium ion secondary battery negative electrodes of Examples 9 to 16 were less likely to deteriorate in discharge capacity even when rapid charging was repeated.
[0281] On the other hand, in the negative electrodes of the lithium ion secondary batteries of Comparative Examples 10, 11, 15, and 16, while S(BET) is within the range of the present invention, I(4.8K) / S(BET) is outside the range of the present invention. In the negative electrodes of the lithium ion secondary batteries of Comparative Examples 12 and 13, I(4.8K) / S(BET) is within the range of the present invention, whereas S(BET) is outside the range of the present invention. In the negative electrodes of the lithium ion secondary batteries of Comparative Examples 9 and 14, both S(BET) and I(4.8K) / S(BET) are outside the range of the present invention. In all of the lithium ion secondary batteries of Comparative Examples 9 to 16, the "discharge capacity retention rate (%) after repeated charging and discharging at -10°C" was 64% or less, and it was confirmed that the discharge capacity was more likely to deteriorate than in Examples 9 to 16.
[0282] In addition, for the negative electrode of the lithium ion secondary battery of Comparative Example 9, an artificial graphite material obtained by using heat-treated raw coal powder whose volatile content is outside the range of less than 3.71% is used. The negative electrodes of the lithium ion secondary batteries of Comparative Examples 12, 13, and 14 had a true density of 1.22 g / cm 3 Super 1.73g / cm 3 In the past, artificial graphite materials have been used that are obtained using heat-treated raw coal powder that is outside the above range. The negative electrodes of the lithium ion secondary batteries of Comparative Examples 10, 15, and 16 had a volatile content outside the range of less than 3.71% and a true density of 1.22 g / cm 3 Super 1.73g / cm 3 In the past, artificial graphite materials have been used that are obtained using heat-treated raw coal powder that is outside the above range. The negative electrode of the lithium ion secondary battery of Comparative Example 11 uses an artificial graphite material obtained by using raw coal powder that has not been heat-treated and has a volatile content outside the range of less than 3.71%. [Industrial Applicability]
[0283] A lithium ion secondary battery having a negative electrode containing the artificial graphite material obtained by the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to the present invention is resistant to deterioration in discharge capacity even when repeatedly charged and discharged at a low temperature of −10° C. Therefore, a lithium ion secondary battery having a negative electrode containing the artificial graphite material obtained by the method for producing an artificial graphite material for a lithium ion secondary battery negative electrode according to the present invention can be preferably used for automobiles such as hybrid automobiles, plug-in hybrid automobiles, and electric automobiles, and for industrial purposes such as power storage in system infrastructure. [Explanation of symbols]
[0284] 10. Lithium-ion secondary battery 11...Negative electrode 12...Negative electrode current collector 13...Positive electrode 14...Positive electrode current collector 15. Separator 16 Aluminum laminate exterior
Claims
【Request 1】 Nitrogen adsorption specific surface area S (BET) is 2.5 to 6.2 m 2 / g, The X-band electron spin resonance method showed that the absorption spectrum originating from carbon radicals appeared near g = 2.0, and the ratio I(4.8K) / S(BET) of the spin density I(4.8K) (spins / g) calculated from the signal intensity at a temperature of 4.8K to S(BET) was 5.2 × 10 17 ~6.8 x 10 17 spins / m 2 1. An artificial graphite material for a negative electrode of a lithium ion secondary battery, comprising:
Citation Information
Patent Citations
JP1979015684A
Mesocarbon microbead, its production, material for producing negative electrode of lithium secondary cell and lithium secondary cell
JP1997151382A
Carbon for lithium battery negative electrode material
JP1997231974A
Electrode material for secondary battery
JP1998241679A
Low-temperature burned carbon for material of electrode
JP2007019257A